Natural Fiber-Reinforced Hybrid Composites - Fiore, Vincenzo (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
In the last few decades, natural fibers have received growing attention as an alternative to the synthetic fibers used in the reinforcement of polymeric composites, thanks to their specific properties, low price, health advantages, renewability, and recyclability. Furthermore, natural fibers have a CO2-neutral life cycle, in contrast to their synthetic counterparts. As is widely known, natural fibers also possess some drawbacks, e.g., a hydrophilic nature, low and variable mechanical properties, poor adhesion to polymeric matrices, high susceptibility to moisture absorption, low aging resistance, etc. This implies that their applications are limited to non-structural interior products. To overcome this problem, the hybridization of natural fibers with synthetic ones (i.e., glass, carbon, and basalt) or different natural fibers can be a solution. For this reason, extensive research concerning natural-synthetic and natural-natural hybrid composites has been done in the last years. In this context, this book aims to collect some interesting papers concerning the use of natural fibers together with synthetic ones with the aim of obtaining hybrid structures with good compromise between high properties (e.g., mechanical performances, thermal behavior, aging tolerance in humid or aggressive environments, and so on) and environment care.